THE LONG-TERM PERFORMANCE OF INITIAL PUBLIC OFFERINGS IN NASDAQ STOCK MARKET DURING 2002-2005 - Nguyen, Thi_Minh_Hai (2009)
Applying the return measurement and methodology in Khurshed et al (1999) the study found underperformance of long-term IPO in NASDAQ stock exchange during a continuous growth period of the stock market similar to previous literature (i.e. Ibbotson, 1975; Ritter, 1991 and Aggarwal and Rivoli, 1993). This implies that investors should not buy IPO stocks within several first trading days and keep them for three years. Also, the study attempts to relate long term underperformance of IPOs in NASDAQ stock exchange to a full set of variables originated from different explanatory theories. Useful advices to investors in similar markets are concluded from empirical findings. If an investor insists in investing in IPOs in long-term, between two IPO stocks he should not invest the small size one, other elements stay the same. IPO stocks of established firms with higher age and more level of multi-nationality are preferred. In a continuous growth period of stock market, long-term investment in IPO stocks with higher volatility is more profitable.